REINFORCEMENT OF SOCIAL STRATIFICATION THROUGH THE USE OF SPEECH LEVELS IN MADURESE TRANSLATION OF QUR’ANIC DIALOGUE VERSES (State Islamic University (UIN) of Sunan Ampel Surabaya, 2023)
Despite the apparent egalitarian principles and language of the Qur’an, the use of speech level in the Madurese translation’s dialogue verses appears to reinforce social stratification, which has existed for a long in society. The current article seeks to map the typology of relationships underlying the use of speech level, its determinant factors and implications. To achieve this, a critical discourse analysis was employed, with the main source being one version of the Qur’anic Madurese translation published by the Indonesian Ministry of Religious Affairs in 2018. Close reading of the verses to gather representative samples, coding, categorization mapping, analysis, and creative synthesis-making were all part of the analysis process. The findings suggest that there are two main types of relationship patterns: hierarchical and egalitarian. These patterns are influenced by factors such as social status, family connections, and the surrounding circumstances. The former focuses on the manifestation of cultural nuances in the translations of the verses, whereas the latter is primarily concerned with the impact on real-life social dynamics.